Application of Learning Models Gamification With the help of Wordwall Media on theoretical material about the entry of Hindu-Buddhist in Indonesia - Rizki, Fatiha; Sumantri, Pulung; Gultom, Imelda Megawati (Jurnal Akuntansi Hukum dan Edukasi, 2024)
Study done For look for answer will a problem with he gave an action in the form of a considered solution can solve problem the.  Study with title Application of Learning Models Based Gamification Assisted by Wordwall Media The aims of students' history learning outcomes in theoretical material on the arrival of Hindu-Buddhism in Indonesia in class X at SMAN 14 Medan For know influence use of wordwall media with a learning model based game to improvement results student History learning.  Research conducted by researchers started with arrangement formulation problems that have made based on apparition real in the field schooling place carry out introduction field schooling.  As for who became background behind so that did it study is there is a number of problem studying in class which hinders the process learning so that No Again deemed optimal. Consequence from problem the make results Study participant educate experience significant decrease. Demonstrative activities problem in class is like student No capable answer question cognitive with OK,  then student not enough control Study material,  students No has the above Solution problems faced,  values students on the material theory the arrival of Hindu-Buddhist in Indonesia is still classified low,  the task is done still on the verge mark not enough until Enough.  This matter happen because at the time delivery material by the teacher to participant educate not in the optimal phase,  Where is the remainder No Can absorb with Good the knowledge provided and teachers are lacking appropriate select the media or model in carry out learning,  planning prepared by the teacher is not can fulfil need Study participant educate so that results given ending No satisfying too. Therefore That researcher endeavor provide solutions with hit the media wordwall and play interesting game for students interested with learning and creating impression more different easy understood and remembered by participants educate.  Collection,  processing and analysis of data in study This done with use method quantitative,  Where is the answer end in study served with systematic figures so that the result nature objective and descriptive circumstances real in the field study.  Type of research used is Classroom Action Research or PTK in it through two cycles research,  cycle second done For perfect values or average that does not pass the cycle first,  each cycle arranged over two series each meeting 2 hour lesson duration.  Compiled classroom action research on a number of stage ie planning,  giving action, observing and reflecting.  Subject in study This is class X 2 SMAN 14 Medan consisting of of 38 students in one class unit.  Deep data analysis study This state that application of Wordwall media based learning gamification can increase results Study students on the material theory the entry of Hindu Buddhism in Indonesia in class X 2 at SMAN 14 Medan, with calculation results ie Based on the results of the data obtained above, it appears that there has been a significant change after the implementation of the gamification-based learning model assisted by wordwall media in students' understanding as seen from the learning outcomes by answering multiple choice questions with a score of 10-100. At the first and second meetings of the first cycle, the average scores were obtained. The average value was 72 with this value still below the KKM, so adjustments were given to the application of the model and media in the second cycle, where the average value obtained increased to 89, where the value had passed the KKM threshold of 75 and stated that the model and media had an influence. the positive.